2020
DOI: 10.1007/s40336-020-00387-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of chest computed tomography scan in diagnosis of COVID-19; a systematic review and meta-analysis

Abstract: Purpose Real-time polymerase chain reaction (RT-PCR) and chest computed tomography (CT) scan are main diagnostic modalities of coronavirus disease 2019 (COVID-19). However, there is still no consensus on which of these methods is superior to the other. Therefore, the present meta-analysis was designed to answer to the question whether CT scan can be used in diagnosis of COVID-19 or not. Methods Searches were performed in Medline, Embase, Scopus, and Web of Science databases until the end of April 2020. Two res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
(21 reference statements)
0
21
0
2
Order By: Relevance
“…We describe use of thoracic computed tomography (CT), because of its role in diagnosis of COVID-19, 17 and in-hospital use of antibiotics that are known to be used for respiratory infections (see Appendix 1), [18][19][20] anticoagulants and systemic corticosteroids, as captured by medication orders after admission. Use of these medications may be associated with COVID-19, 21,22 although our study period was before the publication of the RECOVERY trial's results regarding dexamethasone.…”
Section: Outcomes and Process Measuresmentioning
confidence: 99%
“…We describe use of thoracic computed tomography (CT), because of its role in diagnosis of COVID-19, 17 and in-hospital use of antibiotics that are known to be used for respiratory infections (see Appendix 1), [18][19][20] anticoagulants and systemic corticosteroids, as captured by medication orders after admission. Use of these medications may be associated with COVID-19, 21,22 although our study period was before the publication of the RECOVERY trial's results regarding dexamethasone.…”
Section: Outcomes and Process Measuresmentioning
confidence: 99%
“…There have also been reports that findings of GGO are more common than consolidation in asymptomatic cases, whereas the opposite was observed in symptomatic patients[ 37 ]. The sensitivity and specificity for the diagnosis of COVID-19 using CT scans is highest if GGO is observed simultaneously to one or more of the other aforementioned CT features (specificity: 89%, sensitivity: 90%)[ 38 ]. The diagnostic odds ratio of GGO with at least one other feature is reported as 20, and is significantly higher than any sign in singularity.…”
Section: Imaging For Pulmonary Manifestations Of Covid-19mentioning
confidence: 99%
“…In summary, the need for incorporating this CT protocol to the PET/CT should be considered given the relevance of precisely evaluating lung parenchyma, especially in patients who have not had a thoracic CT scan recently. A recent published meta-analysis focused on the diagnostic performance of CT in the diagnosis of COVID-19 demonstrated that observation of ground glass opacities and other radiological features of viral pneumonia at CT scan had optimum performance in detection of COVID-19 [20]. However, it is suggested to make the final diagnosis based on both CT scan and RT-PCR, as none of these diagnostic tests are reliable alone [20].…”
Section: -[ 18 F]mentioning
confidence: 99%